HUBUNGAN PERSEPSI HARGA DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN: STUDI STATISTIK PADA CRYSTAL LIM - Lydia Mulyani (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2026)
The demand for premium crystal products with both spiritual and aesthetic value has increased in recent years, particularly through social media. However, limited research has examined the factors that drive customer satisfaction in the context of spiritual-premium products. This study aims to assess the influence of price perception and product quality perception on customer satisfaction with Crystal Lim, a premium crystal business in Indonesia. A quantitative cross-sectional survey was conducted with 100 respondents who had purchased Crystal Lim products within the past 12 months. Data were collected through an online questionnaire and analyzed using multiple linear regression. The results show that price perception (β = 0.314; p = 0.002) and product quality perception (β = 0.283; p < 0.001) significantly affect customer satisfaction. The regression model explains 22.6% of the variance in customer satisfaction (R² = 0.226; F(2,97) = 14.165; p < 0.001).